Endophytic bacterial community dynamics in sweet cherry in vitro shoot culture and their role in shoot adaptation after cryopreservation - Jurgita Vinskienė; Inga Tamošiūnė; Rytis Rugienius; Elena Andriūnaitė; Vidmantas Stanys; Danas Baniulis (BMC Plant Biology)
Abstract Background In vitro cultivation and cryopreservation techniques are essential tools for genetic diversity conservation and pathogen-free plant propagation of horticultural crops. The optimisation of cryopreservation protocols typically focuses on minimising the negative effects of pretreatment with cryoprotectors (CPs), cryogenic freezing (CF) treatment, and recovery procedures on explants. However, the impact of in vitro and CF techniques on plant-associated microbiota remains poorly understood, and their potential to improve plant adaptation after cryopreservation is underexplored. The aim of the present study was to investigate in vitro shoot culture and cryopreservation-induced changes in the endophytic bacterial diversity of two sweet cherry cultivars and to assess the potential of an inoculum of bacterial isolates to improve the growth of shoot culture after CF. Results Cultivars ‘Sunburst’ and ‘Mindaugė’ showed different responses to cold hardening preconditioning as well as different survival and regrowth rates after cryopreservation. Metataxonomic analysis revealed variation in the abundance and taxonomic composition of bacteria assigned to 35 families in samples of field-grown tree leaves, dormant buds, and in vitro shoot culture before and after CF treatment. Bacillaceae and Enterobacteriaceae bacteria were predominant in the leaf samples of both cultivars. For ‘Sunburst’, Pseudomonadaceae and Sphingomonadaceae bacteria were dominant in dormant buds and in vitro shoots, respectively, while Burkholderiaceae was largely predominant in the shoots following CF treatment. Conversely, ‘Mindaugė’ tissues exhibited more consistent colonisation by Bacillaceae and Enterobacteriaceae across the experimental groups, except for in vitro shoots where Mycobacteriaceae prevailed. A pure bacterial isolate inoculum was applied to the ‘Mindaugė’ shoot culture to counter the CF treatment-induced suppression of shoot growth (~ 40%). Cocultivation with Brevibacterium sp. S1-2, Bacillus cereus S1-3, or B. toyonensis Nt18 increased the shoot leaf area from 48 to 75%. Conclusions This study revealed that endophytic bacterial diversity is significantly reduced under in vitro conditions, often leading to a genotype-specific increase in the abundance and dominance of bacteria attributed to a single bacterial family. Moreover, shoot cocultivation with endophytic bacterial isolates has potential for improving the recovery of in vitro shoots after cryopreservation.